Early Detection and Preventive Education of Anemia in Pregnant Women through the Consumption of Purple Sweet Potato Biscuits at Sahabat Bunda Clinic - Sri Wulan; Riris Sitorus; Nawa Kurnia Anggraini Siregar; Dea Febriana (JURNAL PENGMAS KESTRA (JPK), 2026)
Anemia among pregnant women remains a significant public health concern both globally and in Indonesia, with serious consequences for maternal and fetal health. This condition may lead to complications during pregnancy and childbirth and can adversely affect fetal growth and development. Therefore, comprehensive preventive efforts are needed, including enhanced health education, regular early screening, and appropriate nutritional interventions to reduce the prevalence of anemia and improve maternal health outcomes. This community service activity aimed to improve pregnant women’s knowledge about anemia, conduct early detection, and provide nutrition intervention based on local food sources. The activity was conducted at Klinik Sahabat Bunda, Deli Serdang Regency, involving 12 pregnant women. The methods used included hemoglobin (Hb) level examination, health education through lectures and interactive discussions, and the provision of purple sweet potato biscuits as a nutritious supplementary food. The results showed that 4 out of 12 pregnant women were anemic (Hb <11 g/dL). After the educational session, participants demonstrated improved understanding, indicated by active participation in discussions and the ability to re-explain the material. The purple sweet potato biscuit intervention also received positive responses as an alternative nutritional source. This activity demonstrates that the combination of early detection, health education, and the utilization of local food is effective in increasing awareness and knowledge of pregnant women regarding anemia prevention. It is expected that similar programs can be continuously developed as a sustainable effort to reduce the prevalence of anemia in pregnant women.